2018
DOI: 10.1038/s41467-018-06519-0
|View full text |Cite
|
Sign up to set email alerts
|

Precisely measured protein lifetimes in the mouse brain reveal differences across tissues and subcellular fractions

Abstract: The turnover of brain proteins is critical for organism survival, and its perturbations are linked to pathology. Nevertheless, protein lifetimes have been difficult to obtain in vivo. They are readily measured in vitro by feeding cells with isotopically labeled amino acids, followed by mass spectrometry analyses. In vivo proteins are generated from at least two sources: labeled amino acids from the diet, and non-labeled amino acids from the degradation of pre-existing proteins. This renders measurements diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
308
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 274 publications
(383 citation statements)
references
References 62 publications
31
308
5
Order By: Relevance
“…Moreover, three principles govern the replacement of lost OLs and the parallel emergence of precise and profuse remyelination: First, the trigger of OL differentiation is not the death of the ablated OL itself (which was cleared within 24 hours of ablation), but rather the following demyelination, which was delayed by as many as 50 days (average 32 days). This is in line with other OL ablation paradigms, where myelin-which also on the protein level has an extremely long half-life 55 -can survive long after OLs have died 43 . In our experiments, we observed that the OL processes resealed rapidly after cell body ablation ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, three principles govern the replacement of lost OLs and the parallel emergence of precise and profuse remyelination: First, the trigger of OL differentiation is not the death of the ablated OL itself (which was cleared within 24 hours of ablation), but rather the following demyelination, which was delayed by as many as 50 days (average 32 days). This is in line with other OL ablation paradigms, where myelin-which also on the protein level has an extremely long half-life 55 -can survive long after OLs have died 43 . In our experiments, we observed that the OL processes resealed rapidly after cell body ablation ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Because ELKS levels were significantly reduced at the P7 calyx and undetectable at P9, in contrast to published data in other brain areas that reported a ELKS half-life in the range of 11-13 days (Fornasiero et al 2018), our data indicate that at the calyx of Held ELKS has a half-life of a few days (ß3-4 days). These discrepancies can be explained by the facts that our measurements were performed with an IHC method that could result in some amount of the signal not being detected, and also protein half-lives can differ in the various brain regions (Fornasiero et al 2018) and different cellular environments (Dorrbaum et al 2018) (i.e. in vitro vs. in vivo).…”
Section: A Developmental Role For Cast/elks In Presynaptic Growth and Azcontrasting
confidence: 96%
“…In summary, our results in immature calyx of Held show that CAST is the dominant isoform and ELKS levels are increased in the presynaptic terminal in the absence of CAST. Because ELKS levels are dramatically reduced by P7 with undetectable levels by P9, this indicates that its half-life in the calyx of Held is significantly shorter than previous reports in other brain areas of 11-13 days (Fornasiero et al 2018), and allows analysis of CAST/ELKS function in the immature calyx from P7 onwards.…”
Section: Ablation Of Cast In Calyx Of Held Leads To Increased Levelsmentioning
confidence: 63%
See 1 more Smart Citation
“…The che-1 mRNA and protein half-lives are short compared to reported mRNA halflives in eukaryotes (Fornasiero et al 2018;Sharova et al 2009) and average protein halflives reported in young C. elegans adults (Dhondt et al 2017;Schwanhausser et al 2011).…”
Section: Copy Number and Lifetime Of Che-1 Mrna And Proteinmentioning
confidence: 76%